2004
DOI: 10.1242/jcs.00859
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in α-tubulin promote basal body maturation and flagellar assembly in the absence of δ-tubulin

Abstract: We have isolated suppressors of the deletion allele of δ-tubulin, uni3-1, in the biflagellate green alga Chlamydomonas reinhardtii. The deletion of δ-tubulin produces cells that assemble zero, one or two flagella and have basal bodies composed primarily of doublet rather than triplet microtubules. Flagellar number is completely restored in the suppressed strains. Most of the uni3-1 suppressors map to the TUA2 locus, which encodes α2-tubulin. Twelve independent tua2 mutations were sequenced. Amino acids D205 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
1
20
2
Order By: Relevance
“…Gene silencing of d-tubulin in Paramecium also resulted in loss of the C-tubule without affecting cilia or basal body formation [22]. This requirement for d-tubulin in C-tubule formation and genetic interactions between d-tubulin and a-tubulin [23], lead Li et al [10] to speculate that d-tubulin may be a component of a unique linker they observed between the B-and C-tubules.…”
Section: The Microtubule Scaffoldmentioning
confidence: 99%
“…Gene silencing of d-tubulin in Paramecium also resulted in loss of the C-tubule without affecting cilia or basal body formation [22]. This requirement for d-tubulin in C-tubule formation and genetic interactions between d-tubulin and a-tubulin [23], lead Li et al [10] to speculate that d-tubulin may be a component of a unique linker they observed between the B-and C-tubules.…”
Section: The Microtubule Scaffoldmentioning
confidence: 99%
“…In Chlamydomonas and Paramecium cells defective for δ-tubulin, the C-tubule is often missing and most centrioles are composed of doublet microtubules [1,92]. The requirement for δ-tubulin in C-tubule formation can be bypassed by suppressor mutations in α-tubulin, suggesting that δ-tubulin may be required for triplet stabilization rather than for C-tubule assembly [94]. Furthermore, genes encoding ε- and δ-tubulins are absent from the Drosophila genome, despite the fact that centrioles containing triplet microtubules are formed in this species [95].…”
Section: Initiation Of Centriole Assemblymentioning
confidence: 99%
“…The first of these was ␦-tubulin -a protein associated with basal bodies. In Chlamydomonas, disruption of the gene encoding ␦-tubulin results in loss of the C-tubule of the basal body microtubules (Dutcher and Trabuco, 1998;Fromherz et al, 2003). In Paramecium, silencing of the gene encoding ␦-tubulin similarly results in loss of the C-tubule, but additionally loss of B-and even A-tubules was observed (Garreau de Loubresse et al, 2001).…”
Section: Release Of Cp Constraint In Mutantsmentioning
confidence: 99%